Anaerobic motor skills of players aged 9–15 covered by the program of polish soccer skills - Kalinowski, Paweł; Wegner, Katarzyna; Marek, Marek; Sołtysiak, Tomasz (Biospołeczne uwarunkowania uczestnictwa w kulturze fizycznej i zdrowotnej osób w różnym wieku, 2017)
Introduction. The key element of the footballer’s training is the preparation of the physical performance. Long-term observations have shown tracks in the development of motor skills. In football, anaerobic abilities play a special role in athletic training. It can be assumed that only adequately measured motor skills are a guarantee of dynamic growth.Aim of the study. The aim of this study is to assess the motor skills in the course of biological development of players aged 9–15 taking part in the Polish Soccer Skills programe and their numerical characteristics.Material and methods. The study included 1131 players at the age of 9 (n = 189), 10 (n = 170), 11 (n = 183), 12 (n = 194), 13 (n = 124), 14 (n = 151), 15 (n = 120). The respondents participated in the Polish Soccer Skills programe and had varied professional experience. The starting speed over a distance of 5 meters, run over a distance of 20 meters, power of the lower limbs, agility run and growth were measured. The average descriptive statistics: (X), the minimum (min), maximum (max) and standard deviation (SD) were measured. The study was conducted in July and August 2014 in towns of Spała, Kleszczów and Wałcz.Results and Conclusions. The study concluded that the level of anaerobic abilities are changing with the development of biological development of players taking part in the program of Polish Soccer Skills. The differences in the anaerobic abilities were observed across all age groups.